Internationalisation Factors - Competency, Commitment and Coordination: A Study on Women-Owned SMEs - Nordin, Norfarah; Siti-Nabiha, A.K.; Mohd Noordin, Nur Farah (Journal of Entrepreneurship, Business and Economics; Vol 10 No 2S1 (2022): Theme: Promoting Financial and Household Resilience, 2023)
The purpose of this study is to examine the effect of competency on internationalisation orientation through the mediation of commitment to learning and coordination. This study also examines the moderation effect of length of business in international new ventures (INVs) on the model. This research focused on INVs belongs to women SMEs in Malaysia. Length of business since inception is hypothesised to interact with commitment and coordination, and thus leads to stronger effect on internationalisation orientation. Quantitative research employing a cross-sectional survey is the method chosen for the research design. These hypothesised relationships are tested using mediation effect test whereas, moderation effect test performed using product indicator approach employing Partial Least Squares-SEM technique. Survey data collected from 154 owned by women entrepreneurs. The samples selected based on directories of exporters in Malaysia employing purposive sampling. The research found commitment to learning and coordination are significant mediators transmitting the effect of competency towards internationalization orientation. The moderation effect of length of a business, also found to be significantly strengthens the effect from coordination towards internationalisation orientation, and strengthen the effect of commitment towards internationalization orientation. Research paper Keywords: Women, Internationalisation, Competency, Commitment, Coordination, Small medium-sized enterprise, Women Reference to this paper should be made as follows: Nordin, N., Siti-Nabiha, A. K., & Mohd Noordin, N. F. (2022). Internationalisation Factors - Competency, Commitment and Coordination: A Study on Women-Owned SMEs. Journal of Entrepreneurship, Business and Economics , 10 (2S1), 216–255.